Dimensi Internasional Perlindungan Hak Kekayaan Intelektual Komunal dan Tradisional di Indonesia - Nuraeni Nuraeni; Rona Ikram Putri (Intermestic: Journal of International Studies, 2017)
This article discusses the international dimensions of communal intellectual property rights protection in Indonesia. In this context, UNESCO as an international actor has been actively involving in cultural heritage preservation, including in the case of Batik and Wayang. Nevertheless, the most important issue is how to encourage policymakers to provide an appropriate system in conserving and protecting traditional communities and their heritages. Through the literature review, this study has found that international actors such as UNESCO have contributions in formulating policy framework regarding the efforts of protecting cultural heritage and traditions as part of communal intellectual property rights in Indonesia, especially to provide international legal instruments.